Behavior and emotional problems in children with mental retardation - Soedjatmiko Soedjatmiko; Muzal Kadim; Bambang Madiyono; Mardjanis Said (Paediatrica Indonesiana, 2004)
Background Behavior and emotional problems in a mentally re-tarded child can inhibit the educational process of the child.Objectives The aims of this study were to find out the prevalenceof behavior and emotional problems in children with mental retar-dation as reported by parents and to assess associated risk fac-tors consisting of mother’s psychopathology, marital discord, malesex, child’s age, socioeconomic status, and family size.Methods This cross sectional study was carried out on 63 chil-dren with mental retardation in a school for retarded children, SLBC Asih Budi I, from January until March 2003. Parents were inter-viewed at school and home using special questionnaires, the ChildBehavior Checklist (CBCL) and Symptom Checklist-90 (SCL-90).Results The prevalence of behavior and emotional problems inthis study was 52%. The majority of behavior and emotional prob-lems were anxious/depressed (18%) and withdrawn (16%). Malesex and age group of 12-18 year-old were not risk factors of be-havior and emotional problems (OR=0.49, p=0.190 and OR=1.14,p=0.94, respectively) while socioeconomic status, family size, andmother’s psychopathology were risk factors (OR= 4.08, p=0.008;OR=4.17, p=0.014; OR=9.28, p=0.018; respectively). There wasa correlation between behavior and emotional problems of chil-dren and marital discord.Conclusion The prevalence of behavior and emotional problemswas 52% in which the majority was internalizing disorder. Risk fac-tors for behavior and emotional problems were mother’s psycho-pathology, four or more children in the family, low socioeconomicstatus, and marital discord